Design Methodology for Intelligent Technical Systems - Develop Intelligent Technical Systems of the Future - Gausemeier, Jürgen; Rammig, Franz-Josef; Schäfer, Wilhelm

Competitive outcomes and the inner core of NTU market games - Brangewitz, Sonja; Gamp, Jan-Philip (Economic Theory)

TopFed: TCGA Tailored Federated Query Processing and Linking to LOD - Saleem, Muhammad; S. Padmanabhuni, Shanmukha; Ngonga Ngomo, Axel-Cyrille; Iqbal, Aftab; S. Almeida, Jonas; Decker, Stefan; F. Deus, Helena (J. Biomed. Semant.)

Big linked cancer data: Integrating linked TCGA and PubMed - Saleem, Muhammad; R. Kamdar, Maulik; Iqbal, Aftab; S. Padmanabhuni, Shanmukha; F. Deus, Helena; Ngonga Ngomo, Axel-Cyrille (J. Web Semant.)

Overview of CLEF Question Answering Track 2014 - Peñas, Anselmo; Unger, Christina; Ngonga Ngomo, Axel-Cyrille (Information Access Evaluation. Multilinguality, Multimodality, and Interaction - 5th International Conference of the CLEF Initiative, CLEF 2014, Sheffield, UK, September 15-18, 2014. Proceedings)

Question Answering over Linked Data (QALD-4) - Unger, Christina; Forascu, Corina; López, Vanessa; Ngonga Ngomo, Axel-Cyrille; Cabrio, Elena; Cimiano, Philipp; Walter, Sebastian (Working Notes for CLEF 2014 Conference, Sheffield, UK, September 15-18, 2014)

Results of the BioASQ Track of the Question Answering Lab at CLEF 2014 - Balikas, Georgios; Partalas, Ioannis; Ngonga Ngomo, Axel-Cyrille; Krithara, Anastasia; Paliouras, Georgios (Working Notes for CLEF 2014 Conference, Sheffield, UK, September 15-18, 2014)

AGDISTIS - Agnostic Disambiguation of Named Entities Using Linked Open Data - Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille; Röder, Michael; Gerber, Daniel; Athaide Coelho, Sandro; Auer, Sören; Both, Andreas (ECAI 2014 - 21st European Conference on Artificial Intelligence, 18-22 August 2014, Prague, Czech Republic - Including Prestigious Applications of Intelligent Systems {(PAIS} 2014))

conTEXT - A Mashup Platform for Lightweight Text Analytics - Khalili, Ali; Auer, Sören; Ngonga Ngomo, Axel-Cyrille (Proceedings of the AI Mashup Challenge 2014 co-located with 11th Extended Semantic Web Conference {(ESWC} 2014), Crete, Greece, May 27, 2014)

HiBISCuS: Hypergraph-Based Source Selection for SPARQL Endpoint Federation - Saleem, Muhammad; Ngonga Ngomo, Axel-Cyrille (The Semantic Web: Trends and Challenges - 11th International Conference, ESWC 2014, Anissaras, Crete, Greece, May 25-29, 2014. Proceedings)

Unsupervised Link Discovery through Knowledge Base Repair - Ngonga Ngomo, Axel-Cyrille; Ahmed Sherif, Mohamed; Lyko, Klaus (The Semantic Web: Trends and Challenges - 11th International Conference, ESWC 2014, Anissaras, Crete, Greece, May 25-29, 2014. Proceedings)

LinkLion: A Link Repository for the Web of Data - Nentwig, Markus; Soru, Tommaso; Ngonga Ngomo, Axel-Cyrille; Rahm, Erhard (The Semantic Web: ESWC 2014 Satellite Events - ESWC 2014 Satellite Events, Anissaras, Crete, Greece, May 25-29, 2014, Revised Selected Papers)

Hybrid Acquisition of Temporal Scopes for RDF Data - Rula, Anisa; Palmonari, Matteo; Ngonga Ngomo, Axel-Cyrille; Gerber, Daniel; Lehmann, Jens; Bühmann, Lorenz (The Semantic Web: Trends and Challenges - 11th International Conference, ESWC 2014, Anissaras, Crete, Greece, May 25-29, 2014. Proceedings)

conTEXT - Lightweight Text Analytics Using Linked Data - Khalili, Ali; Auer, Sören; Ngonga Ngomo, Axel-Cyrille (The Semantic Web: Trends and Challenges - 11th International Conference, ESWC 2014, Anissaras, Crete, Greece, May 25-29, 2014. Proceedings)

A comparison of supervised learning classifiers for link discovery - Soru, Tommaso; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 10th International Conference on Semantic Systems, SEMANTICS 2014, Leipzig, Germany, September 4-5, 2014)

Towards an open question answering architecture - Marx, Edgard; Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille; Höffner, Konrad; Lehmann, Jens; Auer, Sören (Proceedings of the 10th International Conference on Semantic Systems, SEMANTICS 2014, Leipzig, Germany, September 4-5, 2014)

A service-oriented search framework for full text, geospatial and semantic search - Both, Andreas; Ngonga Ngomo, Axel-Cyrille; Usbeck, Ricardo; Lukovnikov, Denis; Lemke, Christiane; Speicher, Maximilian (Proceedings of the 10th International Conference on Semantic Systems, SEMANTICS 2014, Leipzig, Germany, September 4-5, 2014)

A tool suite for creating question answering benchmarks - Ngonga Ngomo, Axel-Cyrille; Heino, Norman; Speck, René; Malakasiotis, Prodromos (Proceedings of the Ninth International Conference on Language Resources and Evaluation, LREC 2014, Reykjavik, Iceland, May 26-31, 2014)

Introduction to Linked Data and Its Lifecycle on the Web - Ngonga Ngomo, Axel-Cyrille; Auer, Sören; Lehmann, Jens; Zaveri, Amrapali (Reasoning Web. Reasoning on the Web in the Big Data Era - 10th International Summer School 2014, Athens, Greece, September 8-13, 2014. Proceedings)

HELIOS - Execution Optimization for Link Discovery - Ngonga Ngomo, Axel-Cyrille (The Semantic Web - ISWC 2014 - 13th International Semantic Web Conference, Riva del Garda, Italy, October 19-23, 2014. Proceedings, Part I)

Cross-Document Coreference Resolution Using Latent Features - Ngonga Ngomo, Axel-Cyrille; Röder, Michael; Usbeck, Ricardo (Proceedings of the Second International Workshop on Linked Data for Information Extraction {(LD4IE} 2014) co-located with the 13th International Semantic Web Conference {(ISWC} 2014), Riva del Garda, Italy, October 20, 2014)

Time-efficient execution of bounded Jaro-Winkler distances - Dreßler, Kevin; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 9th International Workshop on Ontology Matching collocated with the 13th International Semantic Web Conference {(ISWC} 2014), Riva del Garda, Trentino, Italy, October 20, 2014)

Web-Scale Extension of RDF Knowledge Bases from Templated Websites - Bühmann, Lorenz; Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille; Saleem, Muhammad; Both, Andreas; Crescenzi, Valter; Merialdo, Paolo; Qiu, Disheng (The Semantic Web - ISWC 2014 - 13th International Semantic Web Conference, Riva del Garda, Italy, October 19-23, 2014. Proceedings, Part I)

Named Entity Recognition using FOX - Speck, René; Ngonga Ngomo, Axel-Cyrille (Proceedings of the ISWC 2014 Posters {&} Demonstrations Track a track within the 13th International Semantic Web Conference, ISWC 2014, Riva del Garda, Italy, October 21, 2014)

Multilingual Disambiguation of Named Entities Using Linked Data - Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille; Luo, Wencan; Wesemann, Lars (Proceedings of the ISWC 2014 Posters {&} Demonstrations Track a track within the 13th International Semantic Web Conference, ISWC 2014, Riva del Garda, Italy, October 21, 2014)

AGDISTIS - Graph-Based Disambiguation of Named Entities Using Linked Data - Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille; Röder, Michael; Gerber, Daniel; Athaide Coelho, Sandro; Auer, Sören; Both, Andreas (The Semantic Web - ISWC 2014 - 13th International Semantic Web Conference, Riva del Garda, Italy, October 19-23, 2014. Proceedings, Part I)

Ensemble Learning for Named Entity Recognition - Speck, René; Ngonga Ngomo, Axel-Cyrille (The Semantic Web - ISWC 2014 - 13th International Semantic Web Conference, Riva del Garda, Italy, October 19-23, 2014. Proceedings, Part I)

SAFE: Policy Aware SPARQL Query Federation Over RDF Data Cubes - Khan, Yasar; Saleem, Muhammad; Iqbal, Aftab; Mehdi, Muntazir; Hogan, Aidan; Ngonga Ngomo, Axel-Cyrille; Decker, Stefan; Sahay, Ratnesh (Proceedings of the 7th International Workshop on Semantic Web Applications and Tools for Life Sciences, Berlin, Germany, December 9-11, 2014)

From RDF to Natural Language and Back - Gerber, Daniel; Ngonga Ngomo, Axel-Cyrille (Towards the Multilingual Semantic Web, Principles, Methods and Applications)

Proceedings of the 9th International Workshop on Ontology Matching collocated with the 13th International Semantic Web Conference (ISWC 2014), Riva del Garda, Trentino, Italy, October 20, 2014

A Technical Concept for Plant Engineering by Simulation-Based and Logistic-Integrated Project Management - Gutfeld, Thomas; Jessen, Ulrich; Wenzel, Sigrid; Laroque, Christoph; Weber, Jens (Proceedings of the 2014 Winter Simulation Conference)

A Data Mining Approach to Support a Data-Driven Scheduling System for Air Cargo Terminals - Boxnick, Simon; Lauck, Sebastian; Weber, Jens (Proceedings of the IEEE Asia-Pacific World Congress on Computer Science and Engineering 2014 (APWC on CSE 2014))

Experiments using Meta-Heuristics to Shape Experimental Design for a Simulation-Based Optimization System: Intelligent Configuration and Setup of Virtual Tooling - Weber, Jens; Boxnick, Simon; Dangelmaier, Wilhelm (Proceedings of the IEEE Asia-Pacific World Congress on Computer Science and Engineering 2014 (APWC on CSE 2014))

Applying GPU Programming to Obtain Average AS/RS Performance in Optimal Zoned Aisles - Lauck, Sebastian; Boxnick, Simon; Kopecki, Lukas (Proceedings of the IEEE Asia-Pacific World Congress on Computer Science and Engineering 2014 (APWC on CSE 2014))

Analyzing Supply Chain nodes in Heterogeneous Environments based on Transaction Data with Respect to Independent item Behavior - Lauck, Sebastian; Boxnick, Simon; Kopecki, Lukas (Proceedings of the 2nd International Conference on Advances in Computing, Electronics and Communication (ACEC-2014))

System Thinking: Crafting Scenarios for Prescriptive Analytics - Weber, Jens; Minhee, Cho; Lee, Mikyoung; Song, Sa-kwang; Geierhos, Michaela; Jung, Hanmin (Proceedings of the First International Workshop on Patent Mining and Its Applications (IPAMIN) 2014)

SentiBA: Lexicon-based Sentiment Analysis on German Product Reviews - Dollmann, Markus; Geierhos, Michaela (Konvens 2014 Workshop Proceedings)

Linked Open Data System for Scientific Data Sets - Baeumer, Frederik Simon; Gim, Jangwon; Jeong, Do-Heon; Geierhos, Michaela; Jung, Hanmin (Proceedings of the First International Workshop on Patent Mining and Its Applications (IPAMIN) 2014)

„Ich bin dafür, dass...“ Kinder gewinnen Standpunkte - Büker, Petra (Praxis Deutsch, Sonderheft: Durch die Schuljahre 5/6)

The Development of Intercultural Pedagogy and its Influences on the German Primary School: Conclusions and Perspectives - Hüpping, Birgit; Büker, Petra (Intercultural Education)

Entwicklung einer gemeinsamen Bildungsdokumentation für KiTa und Grundschule: Chancen, Hürden und Gelingensbedingungen aus der Perspektive von Erzieherinnen und Grundschullehrer/innen - Büker, Petra (Individuelle Förderung und Lernen in der Gemeinschaft. Tagungsband zur 21. Jahrestagung der Kommission "Grundschulforschung und Pädagogik der Primarstufe" der Deutschen Gesellschaft für Erziehungswissenschaft. (Jahrbuch Grundschulforschung; Bd.17))

Forschendes Lernen und Studieren in der neuen Grundschullehrerausbildung. Konzepte und Projekte aus NRW - Röhner, Charlotte; Büker, Petra; Bunte, Nicola; Miller, Susanne; Velten, Katrin; Wiesemann, Jutta (Individuelle Förderung und Lernen in der Gemeinschaft. Tagungsband zur 21. Jahrestagung der Kommission "Grundschulforschung und Pädagogik der Primarstufe" der Deutschen Gesellschaft für Erziehungswissenschaft. (Jahrbuch Grundschulforschung; Bd. 17))

Gelingensbedingungen für die Gestaltung von Kooperation. Ausgewählte Ergebnisse aus drei Jahren wissenschaftlicher Begleitung des Modellprojekts "Kinderbildungshaus Paderborn". Vortrag im Rahmen der Veranstaltung zur Auszeichnung der Bildungshaus-Partner durch das Bildungsbüro der Stadt Paderborn - Büker, Petra; Bührmann, Thorsten; Kordulla, Agnes
Oktober 2014

Kind- und Ressourcenorientierung als Kernprinzipien der Grundschulpädagogik und der Inklusion. Beitrag im Rahmen des Symposiums: Grundschulpädagogik und Inklusion. Die neuen Förderpädagogischen Studiengänge in NRW an der 23. Jahrestagung der Kommission Grundschulforschung und Pädagogik der Primarstufe an der Universität Leipzig - Büker, Petra
September 2014

Peer Learning in altersgemischten Lerngruppen im Übergang Kita - Grundschule aus der Perspektive von Kindern. Posterbeitrag an der 23. Jahrestagung der Kommission Grundschulforschung und Pädagogik der Primarstufe an der Universität Leipzig - Büker, Petra; Kordulla, Agnes
September 2014

Quality of peer-interaction in mixed-age learning settings – in the transition process from kin-dergarten to primary school. Poster presentation at the 24th EECERA conference - European Early Childhood Education Research Association. Crete, Greece - Büker, Petra; Kordulla, Agnes
September 2014

Bildung für die Zukunft unserer Kinder. Vortrag im Rahmen des 7. BOW-Gesprächs 2014 (Bildungswerk der ostwestfälisch-lippischen Wirtschaft) im b.i.b. International College in Paderborn - Büker, Petra
September 2014

The common stomach: Organizing task allocation in wasp societies - Hamann, Heiko; Karsai, Istvan; Schmickl, Thomas; Hilbun, Allison (Symposium on Biomathematics and Ecology: Education and Research)

Swarm in a Fly Bottle: Feedback-Based Analysis of Self-organizing Temporary Lock-ins - Hamann, Heiko; Valentini, Gabriele (Ninth Int. Conf. on Swarm Intelligence (ANTS 2014))

Optimal Control with Uncertainty - Seifried, A.; Ober-Blöbaum, S. (Dependability of Self-Optimizing Mechatronic Systems)

Introduction to Self-optimization and Dependability - Trächtler, Ansgar; Hölscher, Christian; Rasche, Christoph; Priesterjahn, Claudia; Zimmer, Detmar; Henning Keßler, Jan; Stahl, Katharina; Flaßkamp, Kathrin; Vaßholz, Mareen; Krüger, Martin; Dellnitz, Michael; Iwanek, Peter; et al. (Dependability of Self-Optimizing Mechatronic Systems)

Methods of Improving the Dependability of Self-optimizing Systems - Seifried, Albert; Trächtler, Ansgar; Kleinjohann, Bernd; Heinzemann, Christian; Rasche, Christoph; Priesterjahn, Claudia; Steenken, Dominik; Ramming, Franz-Josef}; Wehrheim, Heike; Henning Keßler, Jan; Gausemeier, Jürgen; Stahl, Katharin; et al. (Dependability of Self-Optimizing Mechatronic Systems)

Analysis of Swarm Behaviors Based on an Inversion of the Fluctuation Theorem - Hamann, Heiko; Schmickl, Thomas; Crailsheim, Karl (Artificial Life)
A grand challenge in the field of artificial life is to find a general theory of emergent self-organizing systems. In swarm systems most of the observed complexity is based on motion of simple entities. Similarly, statistical mechanics focuses on collective properties induced by the motion of many interacting particles. In this article we apply methods from statistical mechanics to swarm systems. We try to explain the emergent behavior of a simulated swarm by applying methods based on the fluctuation theorem. Empirical results indicate that swarms are able to produce negative entropy within an isolated subsystem due to frozen accidents. Individuals of a swarm are able to locally detect fluctuations of the global entropy measure and store them, if they are negative entropy productions. By accumulating these stored fluctuations over time the swarm as a whole is producing negative entropy and the system ends up in an ordered state. We claim that this indicates the existence of an inverted fluctuation theorem for emergent self-organizing dissipative systems. This approach bears the potential of general applicability.

Self-Organized Collective Decision Making: The Weighted Voter Model - Dorigo, Marco; Hamann, Heiko; Valentini, Gabriele; Lomuscio, Alessio; Scerri, Paul; Bazzan, Ana; Huhns, Michael (Proceedings of the 13th Int. Conf. on Autonomous Agents and Multiagent Systems (AAMAS 2014))
Collective decision making in self-organized systems is challenging because it relies on local perception and local communication. Globally defined qualities such as consensus time and decision accuracy are both difficult to predict and difficult to guarantee. We present the weighted voter model which implements a self-organized collective decision making process. We provide an ODE model, a master equation model (numerically solved by the Gillespie algorithm), and agent-based simulations of the proposed decision-making strategy. This set of models enables us to investigate the system behavior in the thermodynamic limit and to investigate finite-size effects due to random fluctuations. Based on our results, we give minimum requirements to guarantee consensus on the optimal decision, a minimum swarm size to guarantee a certain accuracy, and we show that the proposed approach scales with system size and is robust to noise.

Evolving Prediction Machines: Collective Behaviors Based on Minimal Surprisal - Hamann, Heiko (Int. Conf. on Genetic and Evolutionary Computation (GECCO 2014))

Sorting in Swarm Robots Using Communication-Based Cluster Size Estimation - Birattari, Mauro; Dorigo, Marco; Hamann, Heiko; Garnier, Simon; Montes de Oca, Marco; Solnon, Christine; Stuetzle, Thomas; Ding, Hongli (Ninth Int. Conf. on Swarm Intelligence (ANTS 2014))

Derivation of a Micro-Macro Link for Collective Decision-Making Systems: Uncover Network Features Based on Drift Measurements - Khaluf, Yara; Dorigo, Marco; Hamann, Heiko; Valentini, Gabriele; Bartz-Beielstein, T. (13th International Conference on Parallel Problem Solving from Nature (PPSN 2014))

Evolution of Collective Behaviors by Minimizing Surprise - Hamann, Heiko; Sayama, Hiroki; Rieffel, John; Risi, Sebastian; Doursat, Rene; Lipson, Hod (14th Int. Conf. on the Synthesis and Simulation of Living Systems (ALIFE 2014))

A Swarm Robotics Approach to Task Allocation Under Soft Deadlines and Negligible Switching Costs - Cervera, Enric; Khaluf, Yara; Birattari, Mauro; Hamann, Heiko; Pobil, Angel P. del; Chinellato, Eris; Martinez-Martin, Ester; Hallam, John; Morales, Antonio (Simulation of Adaptive Behavior (SAB 2014))

A Review Corpus for Argumentation Analysis - Wachsmuth, Henning; Trenkmann, Martin; Stein, Benno; Engels, Gregor; Palakarska, Tsvetomira (Proceedings of the 15th International Conference on Intelligent Text Processing and Computational Linguistics)

Glycaemic index: did Health Canada get it wrong? Position from the International Carbohydrate Quality Consortium (ICQC). - Carbohydrate Quality Consortium, International; Jenkins, DJ; Willett, WC; Astrup, A; Augustin, LS; Baer-Sinnott, S; Barclay, AW; Björck, I; Brand-Miller, JC; Brighenti, F; Buyken, Anette; Ceriello, A; et al. (Br J Nutr)

Food intake and overweight in school-aged children in Germany: Results of the GINIplus and LISAplus studies. - Pei, Z; Flexeder, C; Fuertes, E; Standl, M; Buyken, Anette; Berdel, D; von Berg, A; Lehmann, I; Schaaf, B; Heinrich, J; and LISAplus Study Group, GINIplus (Ann Nutr Metab)

Are Requirements for Graduates of Master and PhD Programs in Business and Information Systems Engineering Changing? - Eymann, T.; Kundisch, Dennis

Should I Stay or Should I Go - Eymann, T.; Kundisch, Dennis; Recker, J.

Self-optimization in mechanical and plant engineering - Gausemeier, J {\ "u} rgen; Iwanek, Peter; Va {\ ss} Holz, Mareen; Reinhart, Felix (Industry Management)

Systematics of the virtual commissioning of automated production systems - Br {\ "o} kelmann, Jan

Holistic product protection management - approach to developing future- robust protection concepts - Eckelt, Daniel; Gausemeier, J {\ "u} rgen; Peter, Stefan (10th symposium f { \ "u} r Foresight and Technology Planning)

TRIZ-based potential finding in technology-induced innovation processes - Wall, Marina; Gausemeier, J {\; Peter, Stefan
In order to achieve a sustainable competitive advantage, technology-oriented companies are more than ever asked to identify potentials of technologies for future business at an early stage and to convert them into innovations. Emergent technologies in particular have a high potential for radical innovations. However, the high innovation potential is offset by high market and technology uncertainties, which are caused by incomplete knowledge of the technology potential and development as well as of potential application contexts. In connection with emergent technologies, the finding of potential - i.e. the generation of knowledge regarding the potentials - is essential, as it lays the foundation for the search for potential application contexts. At the same time, this represents a challenge, since conventional market research approaches only have a limited effect here. The question that arises is how technology potentials can be derived in a discursive way. Furthermore, we hypothesize that the TRIZ approach has great potential for this: (1) In a reversal of the TRIZ logic, we see a way of accessing the TRIZ knowledge base via an analogy; (2) In this way, contradictions within the meaning of TRIZ can be determined, which can be addressed by the technology; (3) A continuous specification of the contradictions represents a possibility to infer technology potentials. The present article presents an approach developed at the Heinz Nixdorf Institute for a TRIZ-based potential finding within the framework of technology-induced innovation processes. The approach comprises the three phases of technology analysis, technology foresight and technology potential analysis. Based on the analysis of the current performance of the technology, the future performance is anticipated using the TRIZ development pattern. By reversing the TRIZ logic, technology potentials are finally determined.

Business Model Patterns for Disruptive Technologies - Amshoff, Benjamin; Dülme, Christian; Echterfeld, Julian; Gausemeier, Jürgen

A Scalable Framework for Advanced Driver Assistance Systems Simulation - Abdelgawad, Kareem; Hassan, Bassem; Grafe, Michael; Gräßler, Iris

Telemedizinische Assistenzsysteme - Technik, Markt, Geschäftsmodelle - Gausemeier, Jürgen; Wolf, Bernhard; Clauss, Johannes; Friedrich, Petra; Herzog, Karolin; Lehner, Anne-Christin; Lehner, Markus; Placzek, Markus; Schierbaum, Thomas; Spittler, Thomas; Westermann, Thorsten

Method for the Identification and Comparison of Alternative Process Chains Focusing in Economics Effieciency Analysis During the Conceptual Design of Mechatronic Integrated Devices

A Modular Architecture of a PC-based Driving Simulator for Advanced Driver Assistance Systems Development - Abdelgawad, Kareem; Hassan, Bassem; Grafe, Michael; Gräßler, Iris (In the proceedings of REM 2014, the 15th International Workshop on Research and Education in Mechatronics)

Procedural Generation of Vegetation for a Virtual Test Track - Berssenbrügge, Jan; Stöcklein, Jörg; Koza, Andre; Gräßler, Iris (Proceedings of the ASME 2014 International Design Engineering Technical Conferences & Computers and Information in Engineering Conference})

Methodology for the identification of self-optimising potentials for mechatronic systems - Anacker, Harald; Dumitrescu, Roman; Gausemeier, Jürgen; Iwanek, Peter; Schierbaum, Thomas (Proceedings of 2nd Joint Symposium on System-integrated Intelligence: New Challenges for Product and Production Engineering (SysInt))

VR-based conjoint analysis for the early determination of customer benefits {\ "a} references - Backhaus, Klaus; Gausemeier, J {\ "u} rgen; St ö cklein, J {\ "o} rg; Jasper, Jonas; Westhoff, Katharina; Grafe, Michael
Product innovations are of great strategic importance for securing the long-term competitiveness of companies. Often, however, companies are faced with two core problems when introducing product innovations to the market: There is a lack of a methodology for systematic customer integration in the product development process. In addition, due to their complexity and the novelty of the technologies used, the product concepts exceed the customers' imagination. This means that customers do not evaluate new product concepts objectively because they do not fully understand the product benefits. In this article, a software-supported procedure for early customer integration is presented. The core of the process is a multi-stage limit conjoint analysis with an integrated virtual reality application.

Methodology for reporting Interactions between product and production system in the early phases of product development - a practical example - Petersen, Marcus; Bandak, Shatha; Gausemeier, J {\ "u} rgen; Iwanek, Peter; Schneider, Marcel
Innovative products are based on an interdisciplinary interaction between mechanics, electronics and information technology. The close interplay of the specialist disciplines makes special demands on the development process. For example, a uniform understanding of the specialists is particularly important for an efficient development of the product and the associated production system. Furthermore, the product concept often already determines the production system, even though new production technologies make innovative products possible in the first place. Therefore, the interactions between the product and the production system must be taken into account from the start during development. Currently, the development is mostly carried out separately in the specialist disciplines on the basis of existing methods and systematics, who often do not fully consider the existing interactions. Time-consuming and costly iteration loops are the result. This article therefore addresses the interactions and mutual dependencies between the product and the production system in the early phases of product development, such as an adaptation of the product design due to assembly requirements. The development process of a flashlight serves as an example. First, the interactions are described and analyzed. A methodology is then presented that takes these interactions into account in the context of the integrative development of product and production system in the early phases of product development. The methodology consists of a process model, a specification technique and a software tool. The process model serves as a guideline for the integrative development of product and production system, whereas the specification technology forms the core of the methodology and enables interdisciplinary collaboration of all people involved. For the product concept, the specification technology encompasses the aspects of the environment, application scenarios, requirements, functions, effective structure, behavior and design. The principle solution of the production system is represented by the aspects of production requirements, process sequence, resources and design. The software tool supports the developer in applying the methodology. The methodology presented is then demonstrated using the example product. whereas the specification technology forms the core of the methodology and enables interdisciplinary collaboration of all people involved. For the product concept, the specification technology encompasses the aspects of the environment, application scenarios, requirements, functions, effective structure, behavior and design. The principle solution of the production system is represented by the aspects of production requirements, process sequence, resources and design. The software tool supports the developer in applying the methodology. The methodology presented is then demonstrated using the example product. whereas the specification technology forms the core of the methodology and enables interdisciplinary collaboration of all people involved. For the product concept, the specification technology encompasses the aspects of the environment, application scenarios, requirements, functions, effective structure, behavior and design. The principle solution of the production system is represented by the aspects of production requirements, process sequence, resources and design. The software tool supports the developer in applying the methodology. The methodology presented is then demonstrated using the example product. Active structure, behavior and shape. The principle solution of the production system is represented by the aspects of production requirements, process sequence, resources and design. The software tool supports the developer in applying the methodology. The methodology presented is then demonstrated using the example product. Active structure, behavior and shape. The principle solution of the production system is represented by the aspects of production requirements, process sequence, resources and design. The software tool supports the developer in applying the methodology. The methodology presented is then demonstrated using the example product.

Trade and fertility in the developing world: the impact of trade and trade structure - Gries, Thomas; Grundmann, Rainer (Journal of Population Economics)

Approach for the Realization of a Self-Optimizing Production System - Köchling, Daniel; Gausemeier, Jürgen

The Development of Intelligent Technical Systems by the Integration of Self-Optimization - Iwanek, Peter; Dumitrescu, Roman; Gausemeier, Jürgen

Semantische Technologien im Entwurf mechatronischer Systeme: Effektiver Austausch von Lösungswissen in Branchenwertschöpfungsketten - Gausemeier, Jürgen; Trächtler, Ansgar; Schäfer, Wilhelm; Anacker, Harald; Bauer, Frank; Borcherding, Holger; Dziwok, Stefan; Frank, Ursula; Herden, Rudolf; Hoppe, Gerd; Just, Viktor; Kiele-Dunsche, Markus; et al.
Cooperative cyber-physical systems (CCPS) are driven by the tight coordination between computational components, physical sensors and actuators, and the interaction with each other over system bounds. The software development of CCPS is getting more complex because of the tight integration, heterogeneous technologies, as well as safety and timing requirements. Therefore, new engineering approaches, such as model-driven development methods, are required, along with communication architectures with self-* capabilities. Both will support the developer in specifying such a system effectively and efficiently. However, the application of such techniques to the development of CCPS has not been addressed sufficiently so far. This paper presents an experience report of developing a cooperative delta-robot system that juggles a ball without a central control or camera system. For the development, an intelligent network architecture and model-driven development method for CCPS are applied.

Discursive business model development - Successful positioning in the competitive arena through integrative development of market performance and business { \ "a} ftsmodell - Gausemeier, J {\ "u} rgen; Amshoff, Benjamin (ZWF magazine for ü r economic factory operation)

Approach for Scenario-Based Test Specifications for Virtual Commissioning - Schneider, Marcel; Gausemeier, Jürgen; Schmuedderich, Tanja; Trächtler, Ansgar (Proceedings of the DESIGN 2014 - 13th INTERNATIONAL DESIGN CONFERENCE)

Selbstoptimierung verteilter mechatronischer Systeme auf Basis paretooptimaler Systemkonfigurationen - Münch, Eckehard

Acceleration of Material Flow Simulations - Using Model Coarsening by Token Sampling and Online Error Estimation and Accumulation Controlling - Renken, Hendrik

Ein Beitrag zur Verhaltensantizipation und -regelung kognitiver mechatronischer Systeme bei langfristiger Planung und Ausführung - Hartmann, P.

Vorausschau und Technologieplanung. 10. Symposium für Vorausschau und Technologieplanung, Heinz Nixdorf Institut, 20. und 21. November 2014 - Gausemeier, Jürgen

Ändern sich die beruflichen Anforderungen an Masterabsolventen und Doktoranden der Wirtschaftsinformatik? - Eymann, T.; Kundisch, Dennis

Should I Stay or Should I Go - Herausforderungen und Chancen eines Wechsels zwischen Hochschulsystemen - Eymann, T.; Kundisch, Dennis; Recker, J.

Computer und Internet im Spiegel migrationsspezifischer Disparitäten - Vennemann, Mario; Gerick, Julia; Eickelmann, Birgit (Grundschule in der digitalen Gesellschaft. Befunde aus den Schulleistungsstudien IGLU und TIMSS 2011)

Digitale Lernressourcen und leistungsbezogene Disparitäten von Grundschulkindern - Vennemann, Mario; Eickelmann, Birgit (Grundschule in der digitalen Gesellschaft. Befunde aus den Schulleistungsstudien IGLU und TIMSS 2011)

Schulische Ausstattung mit digitalen Medien in der Grundschule - Gerick, Julia; Vennemann, Mario; Lorenz, Ramona; Eickelmann, Birgit (Grundschule in der digitalen Gesellschaft. Befunde aus den Schulleistungsstudien IGLU und TIMSS 2011)

Zur Rolle der Schulleitung bei der Integration digitaler Medien in Grundschulen - Gerick, Julia; Drossel, Kerstin; Eickelmann, Birgit (Grundschule in der digitalen Gesellschaft. Befunde aus den Schulleistungsstudien IGLU und TIMSS 2011)

Nutzung digitaler Medien im naturwissenschaftlichen Unterricht der Grundschule - Eickelmann, Birgit; Vennemann, Mario (Grundschule in der digitalen Gesellschaft. Befunde aus den Schulleistungsstudien IGLU und TIMSS 2011)

Grundschule in der digitalen Gesellschaft – Konzeption und Inhalt des Bandes - Eickelmann, Birgit; Lorenz, Ramona; Vennemann, Mario; Gerick, Julia; Bos, Wilfried (Grundschule in der digitalen Gesellschaft. Befunde aus den Schulleistungsstudien IGLU und TIMSS 2011)

Wie schätzen Grundschullehrerinnen und -lehrer den Stellenwert digitaler Medien ein? - Eickelmann, Birgit; Lorenz, Ramona (Grundschule in der digitalen Gesellschaft. Befunde aus den Schulleistungsstudien IGLU und TIMSS 2011)

Vorwort der Tagungsleitung - Suhl, Leena; Kundisch, Dennis

Digitale Kluft in der Grundschule? Die Ausstattung und Nutzung digitaler Medien von Kindern vor dem Hintergrund sozialer Disparitäten - Drossel, Kerstin; Gerick, Julia; Eickelmann, Birgit (Grundschule in der digitalen Gesellschaft. Befunde aus den Schulleistungsstudien IGLU und TIMSS 2011)

Digitale Medien in der Grundschule - Deutschland und Österreich im Spiegel der internationalen Vergleichsstudie TIMSS 2011 - Eickelmann, Birgit; Vennemann, Mario; Aßmann, Sandra (Medienimpulse. Beiträge zur Medienpädagogik 2012–2013)

Schwierigkeitsmerkmale von Mathematikabituraufgaben im Zentralabitur aus fachlicher und sprachlicher Perspektive – Experteneinschätzungen und statistische Befunde im Vergleich - Lorenz, Ramona; Kahnert, Julia; Eickelmann, Birgit; Walzebug, Anke (Empirische Bildungsforschung und evidenzbasierte Reformen im Bildungswesen)